2015
DOI: 10.1016/j.biomaterials.2014.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal delivery of platinum with in-situ crosslinkable hyaluronic acid gel for local therapy of ovarian cancer

Abstract: Intraperitoneal (IP) chemotherapy is a promising post-surgical therapy of solid carcinomas confined within the peritoneal cavity, with potential benefits in locoregional and systemic management of residual tumors. In this study, we intended to increase local retention of platinum in the peritoneal cavity over a prolonged period of time using a nanoparticle form of platinum and an in-situ crosslinkable hyaluronic acid gel. Hyaluronic acid was chosen as a carrier due to the biocompatibility and biodegradability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 53 publications
0
60
0
Order By: Relevance
“…This observation was not explained by the attenuation of drug release from the HA gel, since the control group administered with two half doses of cisplatin solution with a week interval (mimicking sustained drug release) showed superior tumor regression compared to the platinum-HA gel-treated group. Given that biological activities of HA gel have been exploited in tissue engineering to support the growth of tissues (25), we suspect that the HA gel, after exhausting platinum, may have partaken in the tumor growth (2). In this regard, it is worthwhile to revisit an earlier study reporting the enhancement of intraperitoneal tumor growth in animals treated with HA (26).…”
Section: Hyaluronic Acidmentioning
confidence: 78%
See 2 more Smart Citations
“…This observation was not explained by the attenuation of drug release from the HA gel, since the control group administered with two half doses of cisplatin solution with a week interval (mimicking sustained drug release) showed superior tumor regression compared to the platinum-HA gel-treated group. Given that biological activities of HA gel have been exploited in tissue engineering to support the growth of tissues (25), we suspect that the HA gel, after exhausting platinum, may have partaken in the tumor growth (2). In this regard, it is worthwhile to revisit an earlier study reporting the enhancement of intraperitoneal tumor growth in animals treated with HA (26).…”
Section: Hyaluronic Acidmentioning
confidence: 78%
“…For example, we have reported that a new chitosan derivative has a unique ability to suppress pro-inflammatory cytokine production from endotoxin-challenged macrophages (1). Moreover, we have delivered platinum into the peritoneal cavity using hyaluronic acid nanoparticles and hydrogels for local chemotherapy of ovarian cancer and found that they rather cause a slight increase in tumor burdens at later time points (2), which suggests a potential involvement of empty carriers and degradation products in the growth of residual tumors. These studies indicate that drug carriers can have biological effects to the host, which may not have been anticipated during the system design or inadvertently ignored in data analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, when these systems were IP instilled in the abdomen of mice bearing SKOV-3 tumors, no enhancement in anti-tumor efficacy was measured compared with a solution of the free drug (i.e. cisplatin solution) [86]. Therefore, these findings do not support the expected synergy between the residence time of the drug and its therapeutic effect.…”
Section: Strategies For Ip Delivery and Sustained Release Of Nanomedimentioning
confidence: 89%
“…Hyaluronic acid (HA) NPs forming PtNPs [86]. These NPs were then loaded on a biocompatible and biodegradable in-situ crosslinkable HA gel (PtNP/gel).…”
Section: Strategies For Ip Delivery and Sustained Release Of Nanomedimentioning
confidence: 99%